Impacts of Short-Term Antibiotic Withdrawal and Long-Term Judicious Antibiotic Use on Resistance Gene Abundance and Cecal Microbiota Composition on Commercial Broiler Chicken Farms in Québec - Turcotte, Catherine; Thibodeau, Alexandre; Quessy, Sylvain; Topp, Edward; Beauchamp, Guy; Fravalo, Philippe; Archambault, Marie; Gaucher, Marie-Lou (Frontiers in Veterinary Science, 2020)
The ever-increasing problem of antibiotic resistance makes routine use of antibiotics in animal production no longer considered as a reasonable and viable practice. The Chicken Farmers of Canada have developed and are implementing an Antimicrobial Use Reduction Strategy which has the ultimate goal of eliminating the preventive use of medically-important antibiotics in broiler chicken and turkey production. However, very little is known about the real overall impact of an antibiotic use reduction strategy in complex ecosystems such as the bird intestine or the commercial broiler chicken farm. The main objectives of the present study were to compare the abundance of antibiotic resistance-encoding genes, characterize the intestinal microbiota composition, and evaluate the presence of Clostridium perfringens, in six commercial poultry farms adopting short-term antibiotic withdrawal and long-term judicious use strategy. Implementing an antibiotic-free program over a 15-month period did not reduce the abundance of many antibiotic resistance-encoding genes, whereas the judicious use of antibiotics over six years was found effective. The short-term antibiotic withdrawal and the long-term judicious use strategy altered the intestinal microbiota composition, with Ruminococcaceae and Lachnospiraceae families being negatively impacted. These findings are in agreement with the lower production performance and with the increased C. perfringens populations observed for farms phasing out the use of antibiotics. Adopting a conventional rearing program on commercial broiler chicken farms selected for specific antibiotic resistance-encoding genes in many barns. This study highlights the potential impacts of different rearing programs in poultry production and will help guide future policies in order to reduce the use of antibiotics while maintaining production performance.